2015
DOI: 10.5851/kosfa.2015.35.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Porcine Placenta Extract Ingestion on Ultraviolet B-induced Skin Damage in Hairless Mice

Abstract: The aim of our study was to evaluate the potential benefits of an oral supplement containing porcine placenta extract (PPE) on skin parameters related to cutaneous physiology and aging. PPEs were administered orally to hairless mice for 12 wk. The effects of oral PPE administration on skin water-holding capacity and Transepidermal Water Loss (TEWL) were similar to those of oral collagen (HYCPU2) administered as a positive control. Magnified photographs and replica images showed a reduction in UVB-induced wrink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Among several MMPs, MMP-1 plays a role in decomposing ECM dermal collagen that is mainly composed of type-1 collagen [ 33 ]. It is well known that natural plants have anti-photoaging effects through increasing collagen production by inhibition of MMP [ 34 , 35 ]. In this study, putgyul extracts decreased MMP-1 production in HDFs in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Among several MMPs, MMP-1 plays a role in decomposing ECM dermal collagen that is mainly composed of type-1 collagen [ 33 ]. It is well known that natural plants have anti-photoaging effects through increasing collagen production by inhibition of MMP [ 34 , 35 ]. In this study, putgyul extracts decreased MMP-1 production in HDFs in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that the injection of human placenta extract into wound boundaries accelerated decrease in wound size [6]. Moreover, oral administration of PPE reportedly reduces UVB-induced wrinkle formation in mice, along with the downregulation of MMP-2 mRNA expression [7]. In addition, studies using skin cells have revealed that human placenta extract accelerates keratinocyte and fibroblast proliferation [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…12 Anthocyanin which also contained in mangosteen peel extract is a powerful antioxidant because of its high reactivity as an electron donor and can stabilize unpaired electrons. 13 dermis compared to controls, but not statistically significant when compared with the placebo group. The insignificant difference in the mean of collagen in rat given the mask of mangosteen peel extract compared to placebo may occur probably because the dosage of mangosteen skin extracts present in the mask is insufficient to cause a statistically…”
Section: Discussionmentioning
confidence: 72%